AMPK-ULK1-Mediated Ferritinophagy Drives Ferroptosis in GLA-Induced Testicular Toxicity - Dianyun Wang; Caiying Zhang; Fan Yang; Yang Hu; Chenghong Xing; Guoliang Hu; Jirong Chen; Yi Li; Penghui Liu; Huabin Cao; Xueyan Dai (Research)
The health problem of infertility has garnered increasing attention, prompting a deeper understanding of its causes. The broad-spectrum and nonselective herbicide glufosinate ammonium (GLA) is widely used in many countries. Previous studies have demonstrated the reproductive toxicity of GLA, but its potential toxic mechanisms remain unclear. Here, mice, Sertoli cells, and Leydig cells were used to create GLA preconditioning models. Results showed that GLA exposure caused morphological and functional damage of sperm. Concurrently, our study revealed that GLA, similar to Erastin, could induce ferroptosis in Sertoli and Leydig cells, as indicated by the dose-dependent increases of intracellular iron levels, lipid peroxidation, and cell death. Additionally, both the lipid ROS scavenger Fer and the iron chelator deferiprone were found to mitigate GLA-induced cell death. Intriguingly, our findings suggested that GLA-induced ferroptosis was dependent on autophagy, as the use of pharmacological inhibitors (3-methyladenine, chloroquine, and bafilomycin A1) or autophagy-related gene 5 gene knockout markedly reduced ferroptosis induced by GLA. We also demonstrated that nuclear receptor coactivator 4 (NCOA4)-mediated ferritinophagy, which involves the autophagic degradation of the primary intracellular iron storage protein ferritin, is essential for GLA-induced ferroptosis by showing that NCOA4 knockdown decreased intracellular iron levels and attenuated lipid peroxidation, eventually alleviating GLA-induced cell death. Moreover, we observed that inhibition of the AMP-activated protein kinase–Unc-51-like kinase 1 (AMPK-ULK1) pathway activity by knockdown of AMPK expression markedly reduced the mitochondrial reactive oxygen species (mtROS) level and alleviated GLA-induced ferroptosis. Collectively, GLA induced excessive mtROS production through activation of the AMPK-ULK1 pathway, triggering excessive autophagy that ultimately led to ferroptosis via NCOA4-mediated ferritinophagy.